Cellular carbon microstructures developed by using stereolithography. (October 2017) - Chen, Xu; Zhao, Guangbin; Wu, Yanlong; Huang, Yajiang; Liu, Yaxiong; He, Jiankang; Wang, Ling; Lian, Qin; Li, Dichen
Abstract: Additive manufacturing has attracted much attention to generate structures containing ordered cells and customized shapes with various materials. A simple method was proposed to develop net-shape cellular carbon microstructures (CCMs) with controllable low shrinkage by using stereolithography. The polymer architectures, made of photosensitive resins, and sodium chloride were directly used as carbon precursors and granular support during carbonization, respectively. In addition, graphite powder was introduced into the granular support, which significantly enhances the mechanical property and electrical conductivity of the CCMs, and low graphite content has no significant effect on the volume shrinkage. The extremely high-porosity CCMs without distortion and breakage were obtained, showing controllable low volume shrinkage (44%–52%) with extremely low carbon yield (6%). The microstructure, mechanical property and electrical conductivity were measured and compared. It was found that the CCMs with graphite particles attaching on their surfaces show smooth surfaces with fewer defects, and possess great mechanical property (compressive stress and elastic modulus are 0.36 Mpa and 23.9 Mpa, respectively) and electrical conductivity (0.43 S/cm), which makes them promising materials for many potential applications. Graphical abstract: